2006
DOI: 10.1093/scan/nsl030
|View full text |Cite
|
Sign up to set email alerts
|

Looking you in the mouth: abnormal gaze in autism resulting from impaired top-down modulation of visual attention

Abstract: People with autism are impaired in their social behavior, including their eye contact with others, but the processes that underlie this impairment remain elusive. We combined high-resolution eye tracking with computational modeling in a group of 10 high-functioning individuals with autism to address this issue. The group fixated the location of the mouth in facial expressions more than did matched controls, even when the mouth was not shown, even in faces that were inverted and most noticeably at latencies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
211
6
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(243 citation statements)
references
References 31 publications
24
211
6
2
Order By: Relevance
“…Our results indicate that autistic children differ from typical children not only in the specific features that they rely upon for these judgments of child and adult faces, but also more generally in the extent to which they demonstrate a flexible and adaptive profile of information use in this domain. These results were striking, even in our small sample of autistic participants—which was comparable to most previous studies in this domain, e.g., Spezio et al (2006) tested nine adults, Spezio et al (2007) tested eight adults, and Neumann et al (2006) tested ten adults. We acknowledge that the trial numbers were relatively small in the context of “classical” bubbles research (e.g., Gosselin & Schyns, 2001) but note that they were not far from the more modest numbers that have led to stable solutions in individual level analyses associated with EEG studies (e.g., Schyns, Petro, Smith, 2007, 2009).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our results indicate that autistic children differ from typical children not only in the specific features that they rely upon for these judgments of child and adult faces, but also more generally in the extent to which they demonstrate a flexible and adaptive profile of information use in this domain. These results were striking, even in our small sample of autistic participants—which was comparable to most previous studies in this domain, e.g., Spezio et al (2006) tested nine adults, Spezio et al (2007) tested eight adults, and Neumann et al (2006) tested ten adults. We acknowledge that the trial numbers were relatively small in the context of “classical” bubbles research (e.g., Gosselin & Schyns, 2001) but note that they were not far from the more modest numbers that have led to stable solutions in individual level analyses associated with EEG studies (e.g., Schyns, Petro, Smith, 2007, 2009).…”
Section: Discussionsupporting
confidence: 90%
“…There is a broad consensus that efficient (i.e., in some sense optimized) information use and flexible processing strategies support typical face expertise, but this link is yet to be empirically tested. It is true that evidence of atypical strategic information use in populations with face reading difficulties are consistent with this notion, for example, autism spectrum disorder (e.g., current study, also Neumann et al, 2006; Spezio et al, 2006, 2007) and prosopagnosia (e.g., Caldara et al, 2005; Xivry et al, 2008). Still these groups demonstrate other, potentially influential visuoperceptual and/or social atypicalities, making it an interesting open question whether this association truly holds and/or extends to the typical population.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Klin et al (2002) used eye tracking methodology to demonstrate that while viewing dynamic images via a movie depicting naturalistic social scenes, individuals with ASD tend to spend more time looking at the mouth region of the face than the eyes. When looking at static emotional faces, reports suggest that: (1) children with ASD have similar fixation patterns as typical children (Van der Geest et al 2002); (2) adults with ASD rely more on information from the mouth than the eyes (Neumann et al 2006;Spezio et al 2007a); (3) adults with ASD show less specificity in fixation to the eyes and mouth, that is, they do not gaze more at the eyes and moth even when more information is available in the eyes and mouth, respectively (Spezio et al 2007b); and (4) adults with ASD make more saccades away from information in the eyes (Spezio et al 2007b). A recent eye tracking study has also demonstrated that diminished eye gaze to their mother's eyes during a 'Still Face' episode (neutral, expressionless face) distinguished a group of infant siblings at risk for ASD, suggesting that atypical patterns of eye gaze may be an early feature for the development of the disorder (Merin et al 2007).…”
Section: Eye Tracking and Familiar Facesmentioning
confidence: 99%